Liposomes containing bile salts as novel ocular delivery systems for tacrolimus (FK506): in vitro characterization and improved corneal permeation - Dai Y (Dove Medical Press, 2013)
Yikang Dai,1 Rui Zhou,2 Lin Liu,1 Yi Lu,2 Jianping Qi,2 Wei Wu21Department of Ophthalmology, Renji Hospital, School of Medicine, Shanghai Jiaotong University, 2Key Laboratory of Smart Drug Delivery, Ministry of Education and PLA, School of Pharmacy, Fudan University, Shanghai, People's Republic of ChinaAbstract: The objective of this study was to investigate the potential of liposomes containing bile salts as an ophthalmic delivery system for tacrolimus to improve corneal permeability. Liposomes containing bile salts, including sodium taurocholate, sodium deoxycholate, and sodium glycocholate, were produced by the thin-film dispersion method with a particle size of approximately 100 nm and an entrapment efficiency of more than 90%. Less than 5% tacrolimus was released from conventional liposomes and from liposomes containing sodium taurocholate, sodium deoxycholate, or sodium glycocholate over 12 hours. The cellular uptake of conventional liposomes was significantly higher than that of liposomes containing bile salts. However, liposomes containing bile salts exerted a 3–4-fold increase of tacrolimus in ex vivo corneal transport of tacrolimus compared with conventional liposomes. When rabbit eyes were treated with a DiI perchlorate-loaded liposome suspension, liposomes containing bile salts showed fast and sustained penetration across the cornea. Unfortunately, liposomes containing sodium deoxycholate caused toxicity or irritation to both spontaneously derived human corneal epithelial cells and the rabbit cornea. Therefore, liposomes containing sodium taurocholate and sodium glycocholate are potential carriers in ocular drug delivery systems, given their low toxicity and vastly improved permeability.Keywords: liposomes, bile salt, tacrolimus, cornea, sodium taurocholate, sodium deoxycholate, sodium glycocholate